1995
DOI: 10.1128/aac.39.7.1505
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamics of RP 59500 alone and in combination with vancomycin against Staphylococcus aureus in an in vitro-infected fibrin clot model

Abstract: The bactericidal activity and emergence of resistance to RP 59500 (quinupristin/dalfopristin) when it was administered alone and in combination with vancomycin against fibrin clots that have been infected with methicillin-susceptible Staphylococcus aureus ATCC 25923 or methicillin-resistant S. aureus (MRSA) 67 were evaluated in an in vitro pharmacodynamic infected fibrin clot model. Fibrin clots were infected with S. aureus to achieve an inoculum of approximately 10 9 CFU/g. Antibiotics were administered to si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…The IVIEM prepared was a one-compartment model and was equipped with a tube with a cap where the fibrin clot could be attached as previously described (13,20). After 700 ml of CAMHB medium was placed inside the model by using 6 sets in 2 fibrin clots, the study was conducted by eliminating each set during 72 h. The temperature was maintained at 37°C for 72 h, and the medium within the model was stirred well with a stir bar.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The IVIEM prepared was a one-compartment model and was equipped with a tube with a cap where the fibrin clot could be attached as previously described (13,20). After 700 ml of CAMHB medium was placed inside the model by using 6 sets in 2 fibrin clots, the study was conducted by eliminating each set during 72 h. The temperature was maintained at 37°C for 72 h, and the medium within the model was stirred well with a stir bar.…”
Section: Methodsmentioning
confidence: 99%
“…The MIC at which 90% of the isolates tested are inhibited was 1.56 g/ml (15), and some synergistic effect was demonstrated in in vitro studies if it was combined with vancomycin (17,33). However, in vitro study results could not be applied directly to the clinical setting, so many studies with an in vitro infection model have been attempted in recent years (6,13). We used the in vitro infective endocarditis model (IVIEM) to confirm the efficacies of each antibiotic, including vancomycin, arbekacin, and gentamicin, against MRSA and to compare these efficacies to those of vancomycin and gentamicin in combination and vancomycin and arbekacin in combination.…”
mentioning
confidence: 99%
“…It does not exhibit crossresistance with any existing antibiotics (131,250). In vitro studies have demonstrated increased activity of RP 59500 when combined with vancomycin against MRSA (136). However, no synergy was found against VRE when the drug was combined with ampicillin, ciprofloxacin, gentamicin, rifampin, streptomycin, teicoplanin, or vancomycin (L. B.…”
Section: Treatmentmentioning
confidence: 99%
“…Recently, an in vitro pharmacokinetic and pharmacodynamic model has been developed to simulate IE (4,6,15,17,20,22 25,1997). Like the in vivo model, the in vitro model poses a rigorous challenge to antimicrobial agent efficacy, due to the presence of high organism densities in the setting of a complex biomatrix comprising the simulated vegetation.…”
Section: Several Lines Of Evidence Indicate That Platelets Protect Agmentioning
confidence: 99%